Screening of hepatitis B and C viral infection, recognition of risk factors, and immunization of patients against hepatitis B virus: a module developed for effective hepatitis control - Ejaz, Samina; Abdullah, Iqra; Malik, Waqas Nazir; Anjum, Shazia; Ashraf, Muhammad; Akhtar, Naveed; Khan, Aurangzeb; Hameed, Yasir; Usman, Muhammad; Cheema, Usman; Sidiq, Safeena (Frontiers in Public Health, 2023)
Introduction The continually increasing incidence of hepatitis, a worldwide health issue, in Pakistan, has highlighted the need to investigate the epidemiology factors and implement preventive measures accordingly. The purpose of this study was to scrutinize the prevalent and significantly associated risk factors of hepatitis in students and employees, screening them for hepatitis B and C virus and vaccinating them against HBV to make IUB hepatitis free. Methodology A total of 12,912 participants including students (n = 10,948) and employees (n = 1964) were screened for HBV and HCV via immunochromatographic test. Hepatitis- positive participants’ blood samples were further tested and viral load was estimated by quantitative PCR. All the hepatitis-negative participants were vaccinated against HBV. The demographic and risk factors-related data were collected using the questionnaire. Statistical analysis (Chi-square test and bivariate regression analysis) was performed using SPSS software to explore any association between risk factors and hepatitis. Results Results indicated that 662/12912 participants (students = 478/10,948, employees = 184/1,964) tested positive for hepatitis. Among them, HCV was observed to be more prevalent than HBV among the study participants, employees, and students, and viral count was low in both HBV and HCV-infected participants. However, men were more affected than women. The studied risk factors represented higher frequency among hepatitis-positive participants relative to the hepatitis-negative participants. The Chi-square test revealed that students’ gender, history of hepatitis in the family and relatives, dental treatment, sharing cosmetics and shaving blades were significant (p > 0.005) risk factors of hepatitis while in the employees group surgery and age were significant. Moreover, the reused of syringes was found to be associated with hepatitis in both groups. The bivariate analysis helped to identify various new risk factors which were independently, either positively or negatively, associated with hepatitis. Discussion Our study enabled us to recognize different risk factors of hepatitis among the target population. The information thus generated can be usefully applied in planning hepatitis awareness, targeted screening, and effective control programs for other target populations. In general, this module can be further utilized for any other disease.